On the theory of high-Tc superconductivity of doped cuprates - Pogorelov, Y.G.; Loktev, V.M. (Condensed Matter Physics, 2018)
A theoretical analysis is presented on possible effects of disorder by dopants in high-temperature superconducting cuprate perovskites, to define their basic spectra of spin and electronic excitations, and the subsequent
observable properties, especially doping dependence of superconducting order parameter. The central point in
the proposed physical picture is formation of specific impurity subband within the insulating bandgap of initial
undoped material, serving as a source for the system metallization and further transition into superconducting
state with anisotropic order parameter. Здiйснено теоретичний аналiз можливих ефектiв, спричинених у високотемпературних надпровiдних мiдних перовскiтах присутнiстю допантiв. Розрахованi основнi спектри спiнових та електронних збуджень i
спостережуванi властивостi купратiв, насамперед поведiнка параметра порядку залежно вiд концентрацiї
допантiв. Ключова особливiсть запропонованої фiзичної картини полягає у формуваннi всерединi дiелектричної щiлини вихiдного недопованого матерiалу специфiчної домiшкової пiдзони, яка слугує джерелом наступних металiзацiї i переходу у надпровiдний стан з анiзотропним параметром порядку.